Proficiency Level and Challenges of Students in Disciplines and Ideas in the Social Sciences - Reneth Mae A. Diaz; Joel M. Bual; Dennis V. Madrigal (LPPM Undiksha, 2024)
The social sciences are essential for students to function in society. Therefore, a proficiency assessment is necessary to check their acquisition of competency. This research aims to assess the level of student proficiency and challenges in Social Science Disciplines and Ideas (DISS) in private high schools. Additionally, this study investigated differences in their proficiency levels compared to gender and grades. This type of research is quantitative research. This research uses a quantitative research design, specifically a descriptive-comparative approach. The respondents for this research were 144 students who were determined using stratified random sampling. Data analysis techniques use inferential statistics. The results of this research are that students show a developing level of proficiency in DISS, which indicates that these competencies have not been fully mastered. In comparison, there were differences when grouped by gender and level, with women and those scoring 90-100 scoring higher than their peers. Meanwhile, the challenges faced by students in studying DISS are related to teachers, students, student environment, resources, facilities and subject factors. Considering the results, the anchored theory was validated. Therefore, continuous improvement is encouraged to implement content, strategies, and assessments in DISS to develop students' level of proficiency in the course.